Implementation of Muhadharah Activities and Arabic Language Week to Improve the Arabic Language Ability of Students at Al-Ittihad Islamic Boarding School, Cianjur - Faqih Maulana Mansyur; Ade Arip Ardiansyah (UIN Sunan Gunung Djati Bandung, 2025)
As an Islamic educational institution, Al-Ittihad Islamic Boarding School Cianjur primarily focuses on teaching the Arabic language. To enhance the Arabic language skills of its students, Al-Ittihad Islamic Boarding School Cianjur organizes various activities, including Muhadharah and Arabic Language Week. This research examines the implementation of Muhadharah and Arabic Language Week at Al-Ittihad Islamic Boarding School Cianjur and their impact on the students' Arabic language skills. The results of the study indicate that both activities have been well-structured and effectively implemented, providing a significant positive impact on the students' Arabic language proficiency. This is evidenced by the improvement in the students' Arabic language skills after participating in Muhadharah and Arabic Language Week. The improvement demonstrates that these activities are effective in enhancing the students' vocabulary, grammar, and speaking skills in Arabic. In conclusion, Muhadharah and Arabic Language Week are appropriate and effective strategies for the language instructors and administrators to enhance the Arabic language skills of students at Al-Ittihad Islamic Boarding School Cianjur. Therefore, these activities should be maintained and further developed to improve the quality of Arabic language education at Al-Ittihad Islamic Boarding School Cianjur. This research also provides recommendations for administrators of other boarding schools to organize similar activities to improve their students' Arabic language skills. Additionally, this study can serve as a foundation for further research on developing effective Arabic language learning strategies in the environment of Islamic boarding schools.